The role of endothelial dysfunction in preterm delivery development - S. V. Korovay (Zaporozhye State Medical University, 2012)
Modern facts of the literature about endothelial dysfunction in pregnant women with miscarriage are represented, the pathogenetic signifi cance of endothelial dysfunction in the development of preterm delivery is shown.